52.6k views
2 votes
For f(x)=3x+1 and get g(x) =x2-6, find (f-g)(x)

2 Answers

2 votes

Answer:

(f - g)(x) = (3x + 1) - (x2 - 6) = 3x + 1 - x2 + 6 = -x2 + 3x + 7

i hope this helps.

User Akita
by
5.6k points
5 votes

For this case we have the following functions:


f (x) = 3x + 1\\g (x) = x ^ 2-6

We must find
(f-g) (x).

By definition we have to:


(f-g) (x) = f (x) -g (x)

So:


(f-g) (x) = 3x + 1- (x ^ 2-6)\\(f-g) (x) = 3x + 1-x ^ 2 + 6\\(f-g) (x) = - x ^ 2 + 3x + 6 + 1\\(f-g) (x) = - x ^ 2 + 3x + 7

Answer:


(f-g) (x) = - x ^ 2 + 3x + 7

User Runny Yolk
by
6.0k points